VD_FINDINFO AA 113/08 - 119/2010 vom 2. September 2010 - VD Tribunal cantonal (2010)
CAUSALITÉ ADÉQUATE, CAUSALITÉ NATURELLE, ACCIDENT, TRAUMATISME CERVICAL | 16 al. 2 LAA, 18 al. 1 LAA, 19 al. 1 LAA, 6 al. 1 LAA, 11 OLAA